Madhyamaka and Yogācāra: allies or rivals? - Garfield, Jay L. (Oxford University Press, 2015)
Machine generated contents note: -- Acknowledgments -- Contributors -- Introduction: Madhyamaka and Yogacara: Allies or Rivals? -- Jay L. Garfield, Jan Westerhoff -- 1) Pratityasamutpada and Dharmadhatu in Early Mahayana Buddhism -- Chaisit Suwanvarangkul -- 2) Language and existence in Madhyamaka and Yogacara: Preliminary reflections -- Mattia Salvini -- 3) Reification and Nihilism: The Three Nature Theory and Its Implications -- Sonam Thakchöe -- 4) The Case for Discontinuity -- Mark Siderits -- 5) "Undigested Pride": Bhaviveka on the Dispute Between Madhyamaka and Yogacara -- David Eckel -- 6) Xuanzang and Kuiji on Madhyamaka -- Dan Lusthaus -- 7) Nagarjuna's Yogaaa -- Jan Westerhoff -- 8) Nagarjuna the Yogacarin? Vasubandhu the Madhyamika? On the Middle-way between Realism and Anti-Realism -- Eviatar Shulman -- 9) Without Karma and Nirvana, Buddhism is Nihilism: The Yogacara Contribution to the Doctrine of Emptiness -- Jonathan C. Gold -- 10) Two Topics Concerning Consciousness in Santaraksita's Yogacara-Madhyamaka Syncretism -- James Blumenthal -- 11) I am a Brain in a Vat (Or Perhaps a Pile of Sticks By the Side of the Road) -- Jay L. Garfield -- Index